2016
DOI: 10.3390/jcm5120113
|View full text |Cite
|
Sign up to set email alerts
|

Diaphragm Dysfunction: Diagnostic Approaches and Management Strategies

Abstract: The diaphragm is the main inspiratory muscle, and its dysfunction can lead to significant adverse clinical consequences. The aim of this review is to provide clinicians with an overview of the main causes of uni- and bi-lateral diaphragm dysfunction, explore the clinical and physiological consequences of the disease on lung function, exercise physiology and sleep and review the available diagnostic tools used in the evaluation of diaphragm function. A particular emphasis is placed on the clinical significance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
109
1
14

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 144 publications
(141 citation statements)
references
References 183 publications
1
109
1
14
Order By: Relevance
“…Assessing its mobility is important to detect malfunctions or impending exhaustion and to evaluate the effects of many chest and abdominal conditions on respiratory mechanics [1]. Diaphragm dysfunction is associated with respiratory insufficiency and poorer outcomes [2].…”
Section: Introductionmentioning
confidence: 99%
“…Assessing its mobility is important to detect malfunctions or impending exhaustion and to evaluate the effects of many chest and abdominal conditions on respiratory mechanics [1]. Diaphragm dysfunction is associated with respiratory insufficiency and poorer outcomes [2].…”
Section: Introductionmentioning
confidence: 99%
“…Patients who do not recover quickly using simple measures like BiPAP are at risk for prolonged hospital stay, long periods of mechanical ventilation, pulmonary infections, and increased mortality . van Onna et al reported that three out of 60 patients with PNP developed infections, bronchospasm, and neurologic complications.…”
Section: Discussionmentioning
confidence: 99%
“…4,55 Patients who do not recover quickly using simple measures like BiPAP are at risk for prolonged hospital stay, long periods of mechanical ventilation, pulmonary infections, and increased mortality. 31,32 van Onna et al 13 reported that three out of 60 patients with PNP developed infections, bronchospasm, and neurologic complications. Another study found no significant differences between patients who had PNP and matched controls in terms of postoperative arrhythmias, myocardial infarction, or mortality.…”
Section: Discussionmentioning
confidence: 99%
“…Bedside ultrasound assessment of the diaphragm in critically ill patients can also be used to detect diaphragm dysfunction (diaphragm activity is classified as: usual, reduced, or loss of function) [49]. Although it may help the clinician make therapeutic decisions, a possible role in ventilation and weaning from mechanical ventilation has yet to be fully determined [49][50][51][52].…”
Section: Diaphragm Ultrasound (Dus)mentioning
confidence: 99%